Human induced pluripotent stem cell-derived cardiomyocytes for disease modeling and drug discovery - Moriwaki, Taijun; Tani, Hidenori; Tohyama, Shugo (Frontiers in Bioengineering and Biotechnology, 2025)
Human induced pluripotent stem cells (hiPSCs) have emerged as a promising platform for elucidating disease mechanisms and developing new drugs. Over the past 2 decades, it has become possible to efficiently generate large quantities of cardiomyocytes (CMs) from hiPSCs, thereby enabling the reproduction of disease-specific characteristics in culture dishes. Although this technology has the potential to substantially enhance the efficiency of drug discovery and understanding of disease, the immaturity of hiPSC-derived CMs (hiPSC-CMs) has been a major barrier to their widespread adoption. This review discusses the recent advances that address these challenges and explores the potential of hiPSCs to advance disease modeling, elucidate disease mechanisms, and accelerate drug discovery.